Organization Culture and Quality Management System: A Systematic Literature Review - Sanches, Rafael Augusto de Oliveira; Ferreira, Eric de Paula; Parreiras, Fernando Silva (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – Aiming to fulfill the need to consolidate and carry out a critical analysis of the studies developed on Organizational Culture and Quality Management Systems, this study aims to understand the relationship between these concepts through a systematic review of the literature. Design/methodology/approach – This study is descriptive and is predominantly classified as a quantitative approach. Using the systematic literature review technique, publications contained in the Materials Science & Engineering Database, Emerald Insight, OneFile (GALE), Taylor & Francis Online - Journals, ScienceDirect Journals (Elsevier), Elsevier (CrossRef), Directory of databases were analyzed Open Access Journals (DOAJ), MEDLINE / PubMed (NLM), Library & Information Science Collection and Springer (CrossRef) and 22 studies that deal with the topics in an integrated manner were used. Findings – The analysis shows that the Cameron and Quinn (2011) and Hofstede (2003) models are the most used. Regarding the business sectors in which studies were carried out, no research relating to the topics studied in utilities companies had been carried out, with most of the studies (38%) carried out in companies in the industrial sector. Originality/value – With regard to aspects of quality management relating to organizational culture, there is a balance between the hard and soft elements in the literature and that most studies put forward the management levels of companies as the target audience for the data source. Keywords - Organizational Culture, Management System, Quality Management System, Systematic Literature Review.